ANALISIS MAKNA ADJEKTIVA-I YANG MENUNJUKKAN UKURAN DALAM BAHASA JEPANG SEBAGAI POLISEMI : KAJIAN LINGUISTIK KOGNITIF - Abdurachman, Insan Maulana (2021)
ABSTRAK Bahasa Jepang memiliki suatu kekhasan atau keunikan pada kosakatanya. Oleh karena itu, bahasa Jepang memiliki kesulitan untuk memahaminya. Salah satunya adalah kosakata yang memiliki banyak arti atau polisemi (tagigo). Penelitian ini bertujuan untuk mendeksripsikan makna dasar, makna perluasan, hubungan antara makna dasar dan perluasan pada adjektiva-i yang menunjukkan ukuran, seperti pada adjektiva-i takai, hikui, omoi, dan karui. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian deskriptif. Dari hasil analisi dapat disimpulkan 1) Takai memiliki lima makna yaitu: tinggi, besar, mahal, baik dan keras; hikui memiliki empat makna yaitu: rendah, pendek, murah dan buruk; omoi memiliki tiga makna yaitu: berat, lambat, dan ngebass ; dan karui memiliki tiga makna yaitu: ringan, lega dan rileks 2) Makna dasar takai adalah tinggi; makna dasar hikui adalah rendah; makna dasar omoi adalah berat; dan makna dasar karui adalah ringan 3) Hubungan antara makna dasar dan perluasan dari takai, hikui dan omoi menimbulkan perluasan majas metonimi pada semua maknanya, karui kecuali pada perluasan makna pertama yang mengalami perluasan majas metafora, semua makna perluasannya mengalami perluasan majas metonimi. Kata Kunci: Analisis Makna, Adjektiva-I, Ukuran Dalam Bahasa Jepang, Polisemi, Linguistik Kognitif ABSTRACT Compared to Indonesian, Japanese has a peculiarity or uniqueness in its vocabulary. Therefore, Japanese has its own difficulties when we try to understand it. One of them is when trying to understand vocabulary that has multiple meanings or polysemy (tagigo). This study aims to describe the basic meaning, the extended meaning, the relationship between the basic meaning and the expansion meaning of the i-adjectives that indicate size, such as takai, hikui, omoi, and karui.The research method used to solve the problem in this research is descriptive research method. From the analysis, it is concluded that 1) Takai has five meanings, namely: tall, large, expensive, good and hard (voice); hikui have four meanings, namely: low, short, cheap, and bad; omoi also has three meanings, namely: heavy, slow and bass (voice); karui has three meanings, namely: light, relieved and relaxed 2) The basic meaning of takai is high; the basic meaning of hikui is low; the basic meaning of omoi is heavy; and the basic meaning of karui is light 3) If studied using cognitive linguistic studies, the relationship between the basic meanings and the expansion of the adjectives takai, hikui, omoi leads to metonymy expansion of speech to all of its expanded meanings, while in the adjective karui except for the expansion of the first meaning, which is relieved, which experiences metaphorical expansion of figures of speech, all the meaning of the expansion is experiencing a metonymy expansion of figure of speech, all the meanings of the expansion have metonymy expansion of speech. Keywords: Meaning Analysis, I-Adjectives, Measures in Japanese, Polysemy, Cognitive Linguistics